Influence of non-ferrous metals on the structural quality of the high-alloy mild steel 20X2H4A billets received by centrifugal electroslag remelting - P. I. Papkovskiy; A. I. Valko; S. G. Sandomirskii (Литьë и металлургия)
The problem of the formation of cracks and the conditions of their origin in the cast of metal products have been widely studied in world practice, but the real mechanism of this process is not yet clear enough that it could be applied in production. Hot cracks – one of the most common and the most detrimental defects of steel castings, leading to a significant increase in the cost of products. The formation of hot cracks in steel castings depends on many factors, including the chemical composition of steel, the presence of non-metallic inclusions and gases, conditions of deoxidation and solidification of steel, etc. Therefore, special attention in the real conditions of production should be given to the metallurgical side of the issue. There is no quantitative measure of steel purity in the books of steel, which is divided into chemical, defined by the chemical analysis, and metallographic, defined by the content of non-metallic inclusions. The effect of the general purity of steel on the characteristics of destruction is studied sufficiently, but the data on the individual impact of impurities is very incomplete.In many respects, pure steel has a clear advantage over steel with harmful impurities. This applies to all mechanical properties associated with destruction or processes occurring on the edge of grains. The cardinal way of obtaining cleaner steel, including the reduction of impurities of non-ferrous metals, is the use of pure original charge mixture.The article discusses the topical problem of cracking formation after chemical-thermal treatment in the material of sun gears of the second row of quarry dump trucks BELAZ, obtained by the method of CESR rolled steel 20X2H4А, the possible impact of small concentrations of non-ferrous metals (Pb, Zn, Sn, Bi, As, Se) on the development of external and internal cracks in castings and on structural heterogeneity of steel after CESR.The obtained results allowed to draw conclusions about the impact of non-ferrous metals on the formation of cracks in castings and to establish their limited quantitative characteristics. Based on the results, measures have been proposed to minimize the impact of small amounts of non-ferrous metals on the formation of cracks in castings.